Improving Speaking Fluency through Peer Interaction: A Task-Based Perspective - Norpoʻlatova Nozima Yusufxon qizi (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Abstract: This article explores the role of peer interaction in enhancing speaking fluency among English as a Foreign Language (EFL) learners through a task-based approach. Speaking fluency is one of the most challenging aspects of language learning, and traditional teacher-centered methods often fail to provide learners with sufficient opportunities for meaningful communication. Task-Based Language Teaching (TBLT) emphasizes the use of real-life, purposeful tasks that encourage negotiation of meaning and collaborative problem-solving. The study highlights how pair and group activities, role-plays, discussions, and information gap tasks foster active participation, increase confidence, and improve fluency. Evidence from classroom observations, learner interviews, and previous research demonstrates that peer interaction in task-based settings significantly enhances students’ oral competence, reduces anxiety, and promotes learner autonomy. The article concludes with pedagogical recommendations for integrating peer interaction tasks effectively in EFL classrooms.